Pengaruh Electronic Word of Mouth (E-WOM), Citra Destinasi, dan Fasilitas Wisata terhadap Minat Berkunjung Ulang pada Objek Wisata Tanjung Siambang Pulau Dompak Kota Tanjungpinang - Tirani Fransiska Sihombing; Iranita Iranita; Lastri Anggi Fani (Indo Publishing, 2026)
This study aims to examine the influence of Electronic Word of Mouth (E-WOM), Destination Image, and Tourism Facilities on Revisit Intention at Tanjung Siambang Tourist Attraction. This research employed a quantitative method with an associative approach. The sampling technique used was non-probability sampling with a purposive sampling method involving 100 tourists who had previously visited Tanjung Siambang Tourist Attraction. Data were collected through questionnaire distribution and analyzed using multiple linear regression with the assistance of IBM SPSS Statistics Version 32. The results indicate that Electronic Word of Mouth (E-WOM), Destination Image, and Tourism Facilities have a positive and significant influence on Revisit Intention, both partially and simultaneously. These findings suggest that the dissemination of positive information through electronic media, a favorable destination image, and adequate tourism facilities can enhance tourists’ intention to revisit Tanjung Siambang Tourist Attraction.